Associations of maternal nutrition during pregnancy and post‐partum with maternal cognition and caregiving. Issue 2 (2nd November 2017) - Prado, Elizabeth L.; Ashorn, Ulla; Phuka, John; Maleta, Kenneth; Sadalaki, John; Oaks, Brietta M.; Haskell, Marjorie; Allen, Lindsay H.; Vosti, Steve A.; Ashorn, Per; Dewey, Kathryn G.
Abstract: Pregnant and post‐partum women require increased nutrient intake and optimal cognition, which depends on adequate nutrition, to enable reasoning and learning for caregiving. We aimed to assess (a) differences in maternal cognition and caregiving between women in Malawi who received different nutritional supplements, (b) 14 effect modifiers, and (c) associations of cognition and caregiving with biomarkers of iron, Vitamin A, B‐vitamin, and fatty acid status. In a randomized controlled trial ( n = 869), pregnant women daily received either multiple micronutrients (MMN), 20 g/day lipid‐based nutrient supplements (LNS), or a control iron/folic acid (IFA) tablet. After delivery, supplementation continued in the MMN and LNS arms, and the IFA control group received placebo until 6 months post‐partum, when cognition ( n = 712), caregiving behaviour ( n = 669), and biomarkers of nutritional status ( n = 283) were assessed. In the full group, only one difference was significant: the IFA arm scored 0.22 SD (95% CI [0.01, 0.39], p = .03) higher than the LNS arm in mental rotation. Among subgroups of women with baseline low hemoglobin, poor iron status, or malaria, those who received LNS scored 0.4 to 0.7 SD higher than the IFA arm in verbal fluency. Breastmilk docosahexaenoic acid and Vitamin B12 concentrations were positively associated with verbal fluency and digit span forward (adjusting for covariates p s < .05). In this population in Malawi, maternal supplementation with MMN or LNS did not positively affect maternal cognition or caregiving. Maternal docosahexaenoic acid and B12 status may be important for post‐partum attention and executive function.